2013
DOI: 10.1158/0008-5472.can-12-2272
|View full text |Cite
|
Sign up to set email alerts
|

Novel Small-Molecule Inhibitors of Bcl-XL to Treat Lung Cancer

Abstract: Bcl-XL is a major anti-apoptotic protein in the Bcl-2 family whose overexpression is more widely observed in human lung cancer cells than that of Bcl-2, suggesting that Bcl-XL is more biologically relevant and therefore a better therapeutic target for lung cancer. Here, we screened small molecules that selectively target the BH3 domain (aa 90–98) binding pocket of Bcl-XL using the UCSF DOCK 6.1 program suite and the NCI chemical library database. We identified two new Bcl-XL inhibitors (BXI-61 and BXI-72) that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 47 publications
3
59
0
Order By: Relevance
“…We also found that BSN significantly inhibited tumor cell invasion activity in A549 cells, which may be explained by its ability to negatively regulate the expression of MMP-9 and COX-2 proteins. Bcl-2 and Bcl-xl expression are mainly regulated by STAT3 pathway, and these proteins are overexpressed in lung cancer cells [50, 51]. The downregulation of Bcl-2, Bcl-xl and survivin proteins could account for BSN's ability to induce substantial apoptosis in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that BSN significantly inhibited tumor cell invasion activity in A549 cells, which may be explained by its ability to negatively regulate the expression of MMP-9 and COX-2 proteins. Bcl-2 and Bcl-xl expression are mainly regulated by STAT3 pathway, and these proteins are overexpressed in lung cancer cells [50, 51]. The downregulation of Bcl-2, Bcl-xl and survivin proteins could account for BSN's ability to induce substantial apoptosis in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a new Bcl-X L potent inhibitor, A-1155463, has been recently developed using structure-based design which has already shown in vivo activity [57]. Two other Bcl-X L specific inhibitors have shown to be active against lung cancer cells [58]. Importantly, these compounds caused less effect than ABT-737 on platelet reduction.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…By also giving the BCL-XL inhibitor ABT-263, the inhibitory effect on Bim was abrogated and robust apoptosis was observed [55]. Since ABT-263 was found to cause Grade III and IV thrombocytopenia in 41% of patients in a recent Phase II study of small cell lung cancer [56], we developed a novel BCL-XL inhibitor, which is more potent but induces much less toxicity [57] and is currently in testing. Similarly, using a kinome-centered synthetic lethality screen, Sun et al [31] found that targeting HER3 may act synergistically with MEK inhibition in KRAS-mutant cancers including NSCLC.…”
Section: Mek Inhibition-based Combination Therapymentioning
confidence: 99%